2019
DOI: 10.1245/s10434-019-07204-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sentinel Lymph Node Biopsy Enactment for Cutaneous Melanoma

Abstract: Background Over recent years, sentinel lymph node biopsy (SLNB) recommendations in guidelines for cutaneous melanoma have changed considerably. We aimed to assess trends in enactment of SLNB to evaluate to what extent guidelines were adhered to, and to identify clinical and pathological determinants of (non-)adherence. Methods Clinicopathological data from the Dutch nationwide network and registry of histopathology and cytopathology were retrieved from patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
1
24
0
3
Order By: Relevance
“…A recent study in the Netherlands found that for rates of sentinel node biopsy, head and neck melanoma was the only outlier. 18 In this study, patients with head and neck primaries actually received substantially fewer sentinel node biopsies compared with those with primaries in the trunk or extremities. This difference has not been previously explored and could be the focus of future investigation.…”
Section: Head and Neck Primarymentioning
confidence: 85%
“…A recent study in the Netherlands found that for rates of sentinel node biopsy, head and neck melanoma was the only outlier. 18 In this study, patients with head and neck primaries actually received substantially fewer sentinel node biopsies compared with those with primaries in the trunk or extremities. This difference has not been previously explored and could be the focus of future investigation.…”
Section: Head and Neck Primarymentioning
confidence: 85%
“…Although the trend showed an increase in SLNB enactment, from 39.1% in 2003, still only 47.8% of all eligible patients in 2014 underwent SLNB. Variables significantly associated with non-enactment were female gender, older age, and melanoma located on the head and neck 4…”
Section: Presentmentioning
confidence: 99%
“…Приблизно у 7 % пацієнтів діагностується III стадія захворювання, 5-річне виживання у них становить 60,8 %. У 18-25 % таких хворих виникають регіонарні рецидиви захворювання, асоційовані зі значним зниженням показників виживання [7,8]. При цьому регіонарні рецидиви є найчастішим першим проявом прогресування захворювання для пацієнтів із ІІІ стадією і становлять половину всіх випадків рецидивів хвороби [9,10].…”
Section: огляд / Reviewunclassified